QARAQALPAQSTAN RESPUBLIKASI MIYNET RESURSLARÍNÍŃ QÁLIPLESIWINDE DEMOGRAFIYALÍQ FAKTORLAR HÁM XALÍQ MIGRACIYASÍNÍŃ TÁSIRI - Auezov, Omirbay Tazabaevich (SCIENCE and SOCIETY, 2026)
The article examines the impact of demographic factors and population migration on the formation of labor resources in the Republic of Karakalpakstan. It also studies migration processes in the cities and districts of the Republic of Karakalpakstan.